2013
DOI: 10.1007/s11947-013-1221-6
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Recent Developments on Fructooligosaccharide Production and Applications

Abstract: Over the past years, many researchers have suggested that deficiencies in the diet can lead to disease states and that some diseases can be avoided through an adequate intake of relevant dietary components. Recently, a great interest in dietary modulation of the human gut has been registered. Prebiotics, such as fructooligosaccharides (FOS), play a key role in the improvement of gut microbiota balance and in individual health. FOS are generally used as components of functional foods, are generally regarded as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 113 publications
(127 reference statements)
2
109
0
3
Order By: Relevance
“…The fructose/1-kestose and sucrose/1-kestose ratio also changed after transfer to air, suggesting that FOS metabolism is affected by high CO 2 levels. Apart from the well-known health benefits for human, there are many positive aspects related to the presence of fructans in plants (Livingston et al 2009;McIntyre et al 2012;Dominguez et al 2014). They provide protection from the damage caused to cytosolic proteins and cell membranes by severe low temperature (Hoekstra et al 2001).…”
Section: Short-chain Fos (3-5 Sugar Moieties)mentioning
confidence: 99%
“…The fructose/1-kestose and sucrose/1-kestose ratio also changed after transfer to air, suggesting that FOS metabolism is affected by high CO 2 levels. Apart from the well-known health benefits for human, there are many positive aspects related to the presence of fructans in plants (Livingston et al 2009;McIntyre et al 2012;Dominguez et al 2014). They provide protection from the damage caused to cytosolic proteins and cell membranes by severe low temperature (Hoekstra et al 2001).…”
Section: Short-chain Fos (3-5 Sugar Moieties)mentioning
confidence: 99%
“…These classes of enzymes are widely distributed in plants, fungi and bacteria kingdoms and most of them belong to the Glycoside Hydrolase families 32 (GH32) and 68 (GH68) (Olarte et al, 2016). Although, the physical and chemical characteristics of the molecular structure vary in many microorganisms, they all have both hydrolytic and transfer activities (Dominguez et al, 2013).…”
Section: Fructooligosaccharides (Fos) Are Prebiotics With Known Benefmentioning
confidence: 99%
“…45,46 Many reviews may be found in the literature concerning the oligofructose synthesis from inulin and inulinase production [47][48][49][50] ; FOS production from microbial enzymes and related patents [51][52][53][54][55] ; and GOS production from lactose for food applications also using enzymes. 53 Also, this approach may lead to higher oligosaccharides yields since glucose that inhibits oligosaccharides synthesis is used for cell growth. 51 The use of the whole cells is less expensive and less time consuming than the use of purified enzymes.…”
Section: Extraction Production and Purification Of Polysaccharides mentioning
confidence: 99%